Effectiveness and Safety of Triangular Fibrocartilage Complex Injection Regarding Anatomical Landmarks: A Cadaveric Study - Namazi, Hamid; Ghane, Amir; Dehghanian, Amir Reza; Fereidooni, Mehran; Akbarzadeh, Armin (Journal of Wrist Surgery, 2021)
Background Triangular fibrocartilage complex (TFCC) injections can be applied using anatomical landmarks or under the guide of ultrasound (US). US is not always available, and the physician may rely on the anatomical landmarks.Objective The study aims to evaluate the effectiveness and safety of TFCC injection with anatomic landmarks.Methods Forty wrist specimens from cadavers were randomly assigned to four rapid blue stain injection groups as follows: Group A: perpendicular to skin with 5 mm depth; Group B: perpendicular to skin with 10 mm depth; Group C: 45-degree angulation to skin surface, oriented from proximal to distal with 10 mm depth; and Group D: 45-degree angulation to skin surface, oriented from distal to proximal with 10 mm depth. TFCC specimens were excised and evaluated with microscopy, and adjacent neurovascular structures were checked for any injury.Results Injections in group A were more accurate than others, in which 8/10 injections were successful. Group C injections were least accurate in that only 4/10 were successful. The other remaining groups (groups B and D) revealed similar results (5/10 were successful). However, statistical analyses did not show any significant difference (p-value = 0.35). No injury to neurovascular structures was seen.Conclusion Needle placement perpendicular to skin with 5 mm depth and just medial to ulnar styloid can be used as an accurate method of palpation-guided technique for TFCC injections.
Keywords: triangular fibrocartilage; injections; anatomic landmarks; cadaver